2018
DOI: 10.12788/jhm.3106
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Humoral Immunodeficiency in Patients with Community‐Acquired Pneumonia

Abstract: BACKGROUND Immunodeficiency is an underrecognized risk factor for infections, such as community‐acquired pneumonia (CAP). OBJECTIVE We evaluated patients admitted with CAP for humoral immunodeficiency. DESIGN Prospective cohort study SETTING Inpatients PATIENTS, INTERVENTION, AND MEASUREMENTS We enrolled 100 consecutive patients admitted with a diagnosis of CAP from February 2017 to April 2017. Serum IgG, IgM, IgA, and IgE levels were obtained within the first 24 hours of admission. CURB‐65 score and length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It can also have a multi-dimensional effect on patients with schizophrenia. Regarding the significant risks of pneumonia among patients with schizophrenia 1 , it can also compromise immune function, increasing the risk of developing a respiratory infection 2 . In addition, up to 70% of schizophrenia patients have one or more medical comorbidities 3 , and these clinical conditions can increase risk of infection 4 and mortality rates for COVID-19 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It can also have a multi-dimensional effect on patients with schizophrenia. Regarding the significant risks of pneumonia among patients with schizophrenia 1 , it can also compromise immune function, increasing the risk of developing a respiratory infection 2 . In addition, up to 70% of schizophrenia patients have one or more medical comorbidities 3 , and these clinical conditions can increase risk of infection 4 and mortality rates for COVID-19 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although community-acquired pneumonia is nontransmissible, it could indicate immunodeficiency. 3,4 Thus, our search indicated that this population could be at higher risk of developing respiratory infections, especially when comorbid medical conditions and lifestyle risk factors are involved.…”
mentioning
confidence: 99%
“…Streptococcus pneumoniae or Haemophilus influenzae infections in more than one-third of the patients. 12 Valdamalai et al 13 reported a 38% prevalence of hypogammaglobinemia in patients with communityacquired pneumonia. 13 Interestingly, Cowan et al 14 in a retrospective cohort of invasive pneumococcal disease patients, found that 72.2% of those with an underlying hematological malignancy (CLL, lymphoma, and MM) had hypogammaglobulinemia.…”
Section: Hypogammaglobulinemia Fosters Infections Especially Encapsulmentioning
confidence: 99%
“…12 Valdamalai et al 13 reported a 38% prevalence of hypogammaglobinemia in patients with communityacquired pneumonia. 13 Interestingly, Cowan et al 14 in a retrospective cohort of invasive pneumococcal disease patients, found that 72.2% of those with an underlying hematological malignancy (CLL, lymphoma, and MM) had hypogammaglobulinemia. Timely diagnosis before the development of a serious infection is the key to reducing infection burden and is dependent on appropriate screening and recognition of risk factors.…”
Section: Hypogammaglobulinemia Fosters Infections Especially Encapsulmentioning
confidence: 99%